Parents' Attitude towards Child Tuberculosis - Setiawan, Shafanissa Aulia; Rakhmawati, Windy; Hendrawati, Sri; Maryam, Nenden Nur Asriyani (Journal of Nursing Care, 2023)
Tuberculosis remains one of the deadliest infectious diseases in the world. Not only adults are affected from TB, but children too. Treatment adherence of TB in children can be determined of parents’ attitude towards TB. This study aims to describe parents’ attitude towards child TB in Bandung City. This study was a descriptive quantitative study with cross-sectional approach. Total sampling technique was used in this study; with 50 parents of children with TB visiting community health centers in Bandung City participated. This study used questionnaires adapted from WHO guidance in attitude towards TB survey. Data analysis were done using univariate descriptive statistics in the form of frequency distribution. Based on this study, 94% of the respondents considered TB very serious, 46% of the respondents considered TB very serious in their neighborhood, 60% of the respondents were shocked when their children are diagnosed with TB, 98% of the respondents would talk with doctors to discuss about their children’s condition, and 78% of the respondents said the cost of TB treatment is free. It can be concluded that the majority of parents have positive attitude towards child TB. Based on this study, nurses are expected to facilitate and persuade parents into attitude change towards child TB treatment.